2022
DOI: 10.31635/ccschem.021.202101010
|View full text |Cite
|
Sign up to set email alerts
|

Electrophotocatalytic Si–H Activation Governed by Polarity-Matching Effects

Abstract: Trialkylsilanes are important building blocks in organic synthesis; however, their widespread use in redox chemistry is limited by their high oxidation potentials and comparably high bond dissociation energies (BDEs) of Si-H and α-Si-C-H bonds (>92 kcal mol −1 ). Herein, we report a new strategy for Si-H bond homolysis enabled by the synergistic combination of electrooxidation, photoinduced ligand-to-metal charge transfer (LMCT), and radical-mediated hydrogen atom transfer (HAT). Governed by the polarity-match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
34
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 91 publications
0
34
0
Order By: Relevance
“…Such selectivity might stem from the polar effect. 20 Fig. 1 Examples of 4-pyrrolin-2-one alkaloids.…”
Section: Introductionmentioning
confidence: 99%
“…Such selectivity might stem from the polar effect. 20 Fig. 1 Examples of 4-pyrrolin-2-one alkaloids.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, organic electrosynthesis has undergone considerable renaissance, and provided unique reactivities that are not accessible with traditional synthetic methodologies. With these benefits, organic electrosynthesis has widely been employed in the construction of C-C ( Pollok and Waldvogel, 2020 ; Zhang et al, 2021 ), C-O ( Herszman et al, 2019 ; Zhang et al, 2019 ), C-S ( Zhang et al, 2020 ) and C-Si ( Ke et al, 2021 ; Jiang et al, 2022 ) bonds in green manners. In the context of intramolecular C-H aminations, organic electrosynthesis has also showed great synthetic potentials.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, electrochemistry has emerged as an attractive approach in the field of organic synthesis to introduce chemical functionality into organic molecules because of its environmentally benign and practical nature . Synthetic electrochemistry could achieve redox reactions without needing transition-metal catalysts or toxic reagents due to the use of electrons as oxidizing or reducing reagents . In 2019, our research group reported an environment-friendly and efficient electrochemical fluoroalkylation/cyclization of N -aryacryamide to access fluorinated oxindoles and quinolinones with wide functional groups (Scheme c) .…”
Section: Introductionmentioning
confidence: 99%